Comparative Study of the Flavonoid Content in Radix Scutellaria from Different Cultivation Areas in China - Yiying Zheng; Shengnan Zhou; Haokang Zhang; Zongyuan Lu; Ruixue Deng; Yihao Feng; Pu Liu (International Journal of Analytical Chemistry)
Scutellariabaicalensis Georgi, an important perennial herb, is widely distributed and used all over the world. The root of S. baicalensis (Radix Scutellaria) is rich in flavonoids with a variety of bioactive effects and is widely used in clinic. The different geographical and climatic conditions of different cultivated areas of S. baicalensis lead to the differences of the main components in Radix Scutellaria. The main objective of this study was to evaluate the difference of flavonoid content in Radix Scutellaria from different cultivated areas in China. The mobile phase system, elution gradient, detection wavelength, and other chromatographic conditions for high-performance liquid chromatography-diode array detection (HPLC-DAD) determination of 8 flavonoids in Radix Scutellaria were optimized. The contents of flavonoids in 38 samples of Radix Scutellaria collected from seven main genuine cultivated areas were determined, and the correlation between the content, cultivated area, and the biological activities of Radix Scutellaria was compared. The results implied that baicalin, wogonoside, and baicalein were the three main flavonoids with the highest contents in Radix Scutellaria. The content of flavonoids in different cultivated areas was very different, which had significant regionality and was closely related to the natural conditions of various places. The antioxidant and antitumor activities of the extract of Radix Scutellaria were closely related to the content of flavonoids, and high contents of baicalin, wogonoside, and baicalein positively improved biological activities.